Unit costs in health economic evaluations: quo vadis, Austria? - Mayer, S; Łaszewska, A; Simon, J (MDPI, 2022)
Evidence-informed healthcare decision-making relies on high quality data inputs, including robust unit costs, which in many countries are not readily available. The objective of the Department of Health Economics’ Unit Cost Online Database, developed based on systematic reviews of Austrian costing studies, is to make conducting economic evaluations from healthcare and societal perspectives more feasible with publicly available unit cost information in Austria. This article aims to describe trends in unit cost data sources and reporting using this comprehensive database as a case study to encourage relevant national and international methodological discussions. Database analysis and synthesis included publication/study characteristics and costing reporting details in line with the Consolidated Health Economic Evaluation Reporting Standards (CHEERS 2022) with the year of the database launch as the cut-off point to assess how the methods have developed over time. Forty-two full economic evaluations and 278 unit costs were analyzed (2004–2016: 34 studies/232 unit costs, 2017–2022: 8 studies/46 unit costs). Although the reporting quality of costing details including the study perspective, unit cost sources and years has improved since 2017, the unit cost estimates and sources remained heterogeneous in Austria. While methodologically standardized national-level unit costs would be the gold standard, a systematically collated list of unit costs is a first step towards supporting health economic evaluations nationally.